Comparative study on dermatoglyphics in alcoholic patients - Devčić, Sanja, liječnica; Mihanović, Mate, liječnik; Miličić, Jasna; Glamuzina, Ljubomir; Silić, Ante, liječnik (2009)
Abstract: According to the world’s prevalence rate, alcoholism is in the third place after heart and blood vessel diseases and malignant tumors. With the development of neuroscience, the causes of alcoholism’s biological etiologic sources are still being studied. Considering that dermatoglyphics are highly determined by heritage, we contemplated the possibilities of their discrimination in alcoholic patients in relation to phenotypically healthy subjects. We analyzed the quantitative and qualitative dermatoglyphics properties of 100 alcoholic patients without psychiatric comorbidity, who have been cured in the Psychiatric Hospital »Sveti Ivan« two or more times, and those of 100 phenotypically healthy men. Through the t-test we evaluated the heterogeneity of the examined groups. Results showed a statistically significant difference on five examined variables. In the calculation of fluctuating asymmetry measure, we found no statistically significant differences in the correlation of values of the right and the left hand on the tested variables, beside one. Chi-square tests showed that there is no relation between the dermatoglyphic qualitative properties of alcoholic patients and those of the examinees from the comparison group. Despite the indisputable genetic role in the genesis of alcoholism, the analysis of the dermatoglyphics carried out in our study did not show any etiological connection between the results of the test on dermatoglyphics and the appearance of alcoholism
Bibliografija: 41 jed
Sažetak
Keywords: Dermatoglifi -- Alkoholičari